Sodium‐powered stators of the bacterial flagellar motor can generate torque in the presence of phenamil with mutations near the peptidoglycan‐binding region. Issue 6 (17th April 2019) - Ishida, Tsubasa; Ito, Rie; Clark, Jessica; Matzke, Nicholas J.; Sowa, Yoshiyuki; Baker, Matthew A. B.
Summary: The bacterial flagellar motor powers the rotation that propels the swimming bacteria. Rotational torque is generated by harnessing the flow of ions through ion channels known as stators which couple the energy from the ion gradient across the inner membrane to rotation of the rotor. Here, we used error‐prone PCR to introduce single point mutations into the sodium‐powered Vibrio alginolyticus / Escherichia coli chimeric stator PotB and selected for motors that exhibited motility in the presence of the sodium‐channel inhibitor phenamil. We found single mutations that enable motility under phenamil occurred at two sites: (i) the transmembrane domain of PotB, corresponding to the TM region of the PomB stator from V. alginolyticus and (ii) near the peptidoglycan binding region that corresponds to the C‐terminal region of the MotB stator from E. coli. Single cell rotation assays confirmed that individual flagellar motors could rotate in up to 100 µM phenamil. Using phylogenetic logistic regression, we found correlation between natural residue variation and ion source at positions corresponding to PotB F22Y, but not at other sites. Our results demonstrate that it is not only the pore region of the stator that moderates motility in the presence of ion‐channel blockers. Abstract : The bacterial flagellar motor rotates to make bacteria swim. We use directed evolution to explore which parts of the ion channels that drive rotation are important for ion selectivity and function. We used the sodium blocker phenamil to screen for mutations that enable rotation while restricting sodium ion transit. We found motility‐enabling mutations at the pore, but also far from the pore in the peptidoglycan binding region of the ion channels, and examined how frequently and in what species, these mutations naturally occurred.